1792. Assessing Outcomes of Antimicrobial Stewardship Interventions Along With a Hospital-Wide β-Lactam Allergy Guideline Through Aztreonam Use: A 5-Year Observation. (26th November 2018) - Wang, Sheila K; Won, Sarah; Bandi, Sindhura; Tobin, Mary; Beshir, Michael; Ravindran, Shayna; Shields, Beth; O'Driscoll, Tristan; Lu, Hung Li; Hanson, Amy; Varughese, Christy; Segreti, John
Abstract: Background: Aztreonam (AZT) is an alternative antibiotic for Gram-negative infections requiring IV therapy and anti-pseudomonal coverage in patients with an IgE mediated penicillin allergy. However, many reported allergic reactions to penicillins are either unknown or mis-categorized. In 2012, significant use of AZT was observed at our institution coupled with a 29% resistance rate for Pseudomonas aeruginosa (PA) to AZT. The aim of this study was to track and assess AZT use during a 5-year period during which antimicrobial stewardship interventions along with a hospital-wide allergy guideline were implemented to optimize antibiotic use. Methods: A retrospective review of AZT use was conducted at RUSH University Medical Center from January 2012 to December 2017. September of 2012, AZT was restricted for use in patients with an immediate type-1 hypersensitivity reaction to a β-lactam (BL) with approval from the infectious diseases (ID) consult service. January 2015, a hospital-wide BL allergy guideline, including a clinical pathway for BL graded challenges, was implemented. November 2015 and April 2017, computerized order-sets for BL graded challenges and in-patient penicillin skin tests were executed, respectively. AZT usage was tracked yearly and stratified by the number of patient cases, total number of doses and average days of therapy (DOT) to assess for differences. AZT cost, PA susceptibility, BL graded challenges and ID consultations for approval were also tracked for assessment. Results: Patient cases using AZT decreased by 76% in 2017. The total number of doses decreased by 84%. The mean DOT for AZT declined from 5.5 days in 2012 to 3.4 days in 2017. The expenditure of AZT reduced by 86%. Hospital-wide resistance rates for PA to AZT declined to 22% in 2017. Compliance with the BL allergy guideline improved post implementation as the number of BL graded challenges rose to a mean of 30 orders with an 82% decrease in ID consults in 2017. Conclusion: Multiple stewardship interventions, including restrictions and guidelines, can significantly decrease use of AZT and improve susceptibility of PA to AZT. Disclosures: All authors: No reported disclosures.